Establishment of Axenic explants and callus culture of clinacanthus nutants (rumput belalai gajah) - Ng, Li Ying (Universiti Malaysia Sarawak, UNIMAS, 2013)
Clinacanthus nutans (Burm.f.) Lindau (snake grass) of family Acanthaceae is known as a herb, shrub or ornamental grass used for medicinal purposes. Clinacanthus nutans is a famous tropical herb and have been used widely in Southeast Asia especially in Sabah, Malaysia as an anti- inflammatory drug for the treatment of wound, disinfection and cancer. The purpose of this study is to establish an effective surface sterilization protocol and to develop an in vitro propagation of Clinacanthus nutans using plant hormone. The study started with the establishment of axenic explants culture. Shoot tips, internode and leaves from grown seedling of snake grass were as the explants. Resulted showed most of the explants were found damaged by treatment of 15% ‘Clorox®’. The protocol below would result in 93% contamination-free internodes explant in culture. The protocol involves dipping explants first in 70% ethanol for 30 seconds followed by agitating the explants in 10% ‘Clorox®’ for 10 minutes, rinsed at least three times with distilled water and then dipped in 0.1% of benomyl fungicide for one hour, rinsed for three times before culture in half MS medium. Study on callus induction was carried out quite successful. Result showed that BAP alone at 2.0 mg/l is effective in the induction of callus formation. It was found that usingthe plant growth regulators such as 2,4-D and picloram could not be used for callus induction of this plant species. The study of BAP and IBA or NAA effect on shoot induction at different concentration was conducted but no any shoot produced in about six weeks after culturing the callus induced explant in the shoot induction medium. Such protocol needs to be further refined to imporove the efficiency and modified for other types of plant growth regulator.